2014
DOI: 10.1088/1742-6596/500/17/172009
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced hotspot formation and chemical reaction initiation in PETN containing a spherical void

Abstract: Abstract. We present results of reactive molecular dynamics simulations of hotspot formation and chemical reaction initiation in shock-induced compression of pentaerythritol tetranitrate (PETN) with the ReaxFF reactive force field. A supported shockwave is driven through a PETN crystal containing a 20 nm spherical void at a sub-threshold impact velocity of 2 km/s. Formation of a hotspot due to shock-induced void collapse is observed. During void collapse, NO2 is the dominant species ejected from the upstream v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…Figure 3 shows the time evolution of the spatial extent of the dynamically formed hotspots for different pore sizes by tracking the amount of material in the simulation cell above 1700 K. In all cases studied there is an initial sudden rise in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the hot spot area due to the collision of the ejected material with the downstream wall of the pore. The overall behavior described thus far is fairly consistent with current understanding of hot spot formation from continuum modelling and experiments 13,15,23,24,36,[39][40][41] . An important distinction is the initial temperature spike and local non-equilibrium state at short times, which continuum models suppress through limited resolution, artificial viscosity and equilibrated equations of state.…”
Section: Dynamical Hot Spot Formationsupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 3 shows the time evolution of the spatial extent of the dynamically formed hotspots for different pore sizes by tracking the amount of material in the simulation cell above 1700 K. In all cases studied there is an initial sudden rise in 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the hot spot area due to the collision of the ejected material with the downstream wall of the pore. The overall behavior described thus far is fairly consistent with current understanding of hot spot formation from continuum modelling and experiments 13,15,23,24,36,[39][40][41] . An important distinction is the initial temperature spike and local non-equilibrium state at short times, which continuum models suppress through limited resolution, artificial viscosity and equilibrated equations of state.…”
Section: Dynamical Hot Spot Formationsupporting
confidence: 82%
“…Rather than remaining as a separate phase, we expect those gas molecules to intermix with the rarefying RDX and absorb a minor amount of heat from the collision process. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Finally, we note that similar simulations to these have recently been performed with PETN, 24,31 though a full analysis of the reaction processes has not yet appeared. PETN is a more mechanically sensitive material than RDX, and is on the borderline between what are considered primary and secondary explosives.…”
Section: Discussionsupporting
confidence: 57%
“…[25][26][27][28][29] Discrete methods have also been employed. For example, reactive molecular dynamics (MD) simulations have been used to study pore collapse in PETN 30 and fuel oil inclusions in ammonium nitrate, 31 whereas coarse-grained descriptions based on dissipative particle dynamics show promise for such calculations in RDX. 32,33 Previous continuum-based approaches have, for the most part, viewed the mechanical responses of crystalline HE materials as isotropic and independent of the rate of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MD simulations have been used to study square pore collapse that produces jetting [31], the effect of shock strength on the mechanism of collapse [32], and the effect of pore size and arrangement on the minimum piston velocity necessary to produce detonation [33]. Reactive cases have been considered in MD simulations with the ReaxFF reactive force field [34,35] for the energetic materials pentaerythritol tetranitrate (PETN) [36] and ammonium nitrate/fuel oil (ANFO) [37]. In both cases it was observed that the presence of pores led to an enhanced chemical reactivity compared to defect-free material.…”
Section: Introductionmentioning
confidence: 99%